PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Manuari, Ratih; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
Income smoothing’s practice is management company’s effort to reduce fluctuations in so that the profit from income smoothing practices will result in a relatively stable income . This study aims to examine the factors that influence the management’s company to perform income smoothing’s practices contained in the companies listed in Indonesia Stock Exchange 2008-2012 period. The variables tested which include the dividend payout ratio, profitability, financial leverage, the net profit margin and public ownership. The sample selection by the purposive sampling method, so that a total result is 19 manufacturing companies selected. The total observation for 5 years is 95 observations . Eckel index used in this study to identify companies that perform income smoothing practices and who does not perform income smoothing practices. Hypothesis testing is performed by binary logistic regression obtain the result that the net profit margin variables affect income smoothing’s practices while variable dividend payout ratio, profitability, financial leverage and public ownership does not affect the income smoothing’s practices .
Keywords: Income smoothing, dividend payout ratio, profitability, financial leverage, the net profit margin, public ownership and Indonesia Stock Exchange.